Functional neural networks of time perception: Challenge and opportunity for schizophrenia research - Ortuño, Felipe; Guillén-Grima, Francisco; López-García, Pilar; Gómez, José; Pla, Jorge (Schizophrenia research, 2011)
With the double objective of searching for a physiological brain circuit concerned with time estimation and establishing whether this circuit is dysfunctional in schizophrenia patients, we carried out an activation likelihood estimate (ALE) meta-analysis of published functional neuroimaging studies. Our results reproduce the previous finding of a neurophysiological cortico–cerebellar–thalamic circuit related with time estimation in healthy individuals. In schizophrenia patients, the analysis indicates significantly lower activation of most right hemisphere regions of the circuit, suggesting that it may be subject to a pattern of disconnectivity. The ALE-meta-analysis approach is useful and further studies could elucidate how the timing circuit is connected with other cognitive tasks.